2017
DOI: 10.1111/jam.13410
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of anti-microbial and anti-tubercular molecules from Fusarium solani : an endophyte of Glycyrrhiza glabra

Abstract: Aims Glycyrrhiza glabra is a high‐value medicinal plant thriving in biodiversity rich Kashmir Himalaya. The present study was designed to explore the fungal endophytes from G. glabra as a source of bioactive molecules. Methods and Results The extracts prepared from the isolated endophytes were evaluated for anti‐microbial activities using broth micro‐dilution assay. The endophytic strain coded as A2 exhibiting promising anti‐bacterial as well as anti‐tuberculosis activity was identified as Fusarium solani by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…This may support the observation that why a species of endophyte can synthesise a bioactive compound in one plant but is unable to do so when isolated from another host species [12]. This fact is supported by various investigations on many endophytic species like Fusarium, Colletotrichum, Alternaria, Aspergillus, Emericella, Penicillium, Pestalotiopsis, Xylaria, Bacillus, Streptomyces, and some others [2,6,27,[45][46][47][48][49][50][51][52][53][54][55][56][57][58]. In these studies, researchers have reported different important molecules from the same endophyte while isolating it from host plants of different ecoregions.…”
Section: Impact Of Environmental Conditionssupporting
confidence: 66%
“…This may support the observation that why a species of endophyte can synthesise a bioactive compound in one plant but is unable to do so when isolated from another host species [12]. This fact is supported by various investigations on many endophytic species like Fusarium, Colletotrichum, Alternaria, Aspergillus, Emericella, Penicillium, Pestalotiopsis, Xylaria, Bacillus, Streptomyces, and some others [2,6,27,[45][46][47][48][49][50][51][52][53][54][55][56][57][58]. In these studies, researchers have reported different important molecules from the same endophyte while isolating it from host plants of different ecoregions.…”
Section: Impact Of Environmental Conditionssupporting
confidence: 66%
“…Similarly, the expression of pro-inflammatory cytokines such as TNF-α and IL-6 was suppressed after treatment of DEX or 1-9 on LPS-induced macrophage cells ( Figure 5). Compound 1 was previously reported as a phytotoxin, cytotoxin against human cancer cells, a anti-parasitic agent against Trichomonas vaginalis, and an anti-tuberculosis agent [20][21][22][23]. Compound 4 was known with the hepatic glucose production inhibiting activity and cytotoxicity [24].…”
Section: Biological Activities Of Isolated Compoundsmentioning
confidence: 99%
“…exhibited the only week antioxidant property 40 . It indicates that the metabolite profile of fungal endophytes is exclusively dependent on the biochemical environment of the host as well as ecological or environmental conditions 41 .…”
Section: Discussionmentioning
confidence: 99%